Analysis Comparison of Company Financial Performance Before and After Merger in Companies Listed on the Indonesia Stock Exchange - Khaeruddin, Faizah; Sirajuddin, Suharti (Universitas Negeri Makassar, 2024)
This research aims to analyze the impact of mergers carried out on the Indonesia Stock Exchange for 2 years, namely before and after the merger has an effect on company value. The type of research carried out is quantitative descriptive research, meaning it presents a complete portrait of a social phenomenon by including certain variables that are relevant to the problem being studied. The research results show that the merger does not lead to improvements in the company's financial performance. Financial performance in this research uses liquidity, solvency and profitability. There are differences in the liquidity ratio using the current ratio and profitability using the return on equity ratio, but there is no difference in the solvency ratio using the debt to total asset ratio.Penelitian ini bertujuan untuk menganalisis dampak merger yang dilakukan di Bursa Efek Indonesia selama 2 tahun yaitu sebelum dan sesudah merger berpengaruh terhadap nilai perusahaan. Jenis penelitian yang dilakukan adalah penelitian deskriptif kuantitatif, artinya menyajikan potret lengkap suatu fenomena sosial dengan memasukkan variabel-variabel tertentu yang relevan dengan permasalahan yang diteliti. Hasil penelitian menunjukkan bahwa merger tidak mengarah pada peningkatan kinerja keuangan perusahaan. Kinerja keuangan dalam penelitian ini menggunakan likuiditas, solvabilitas, dan profitabilitas. Rasio likuiditas menggunakan rasio current ratio dan profitabilitas menggunakan rasio return on equity terdapat perbedaan. Namun rasio solvabilitas menggunakan debt to total asset ratio tidak terdapat perbedaan.